Mr Ellison helps himself. (Economist, 2009)
The article examines the acquisition of Sun Microsystems by computer software maker Oracle Corp. The $7.4 billion deal surprised many in high technology industries, which expected Sun to be purchased by another computer hardware maker. Larry Ellison, Chief Executive Officer (CEO) of Oracle, has conducted an aggressive merger and acquisition policy, and was eager to acquire Sun's rights to the Java programming language.